Moderating Role of Social Norms in the Relationship between Tax Knowledge, Quality of Tax Service, and Tax Compliance among MSMEs - Della Fadhilatunisa; Muhammad Nurfaizy Hamdan; Andika Isma; Hajar Dewantara; Andi Naila Quin Azisah Alisyahbana (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study addresses the persistent problem of low tax compliance among informal Micro, Small, and Medium Enterprises (MSMEs), which undermines fiscal stability and hampers economic development. The primary purpose of the research is to examine the direct effects of tax knowledge and the quality of tax service on tax compliance, as well as to assess whether social norms moderate these relationships among informal MSMEs. Employing a quantitative approach with a cross-sectional survey design, data was collected from owners and managers of informal MSMEs using structured questionnaires. The analysis was conducted using structural equation modeling (SEM) to test the hypothesized relationships and moderation effects. The results indicate that both tax knowledge and the quality of tax service have significant positive effects on tax compliance behavior among informal MSMEs. However, the moderating role of social norms was not supported, as social norms did not significantly influence the relationships between tax knowledge, service quality, and compliance. These findings imply that policy interventions to enhance tax compliance in the informal sector should prioritize educational initiatives and improvements in service quality, rather than relying primarily on social or communal influences. Despite offering important insights, this study is limited by its cross-sectional design, geographically constrained sample, and reliance on self-reported data, which may affect the generalizability and causality of the findings. Future research should consider broader samples, longitudinal approaches, and the inclusion of additional contextual or psychological factors to deepen the understanding of tax compliance behavior among informal MSMEs.